Best Answer

Restricting the discussion to real numbers for now. In this case, the square root is only defined for non-negative numbers; the principal square root of a positive number is the POSITIVE square root. For example, both +5 and -5 are square roots of 25, since both - when squared - give you 25. But the positive square root (+5) is called the principal square root, and if you write the square root symbol, that's the number usually meant.

🙏

🤨

😮

Study guides

Q: What is X - square root of x?

Write your answer...

Submit

Related questions

Yes, because when x equals 1, the square root of x is rational and the square root of -x is irrational, and when x equals -1, the square root of x is irrational and the square root of -x is rational.

No. The Square root of x is not the value of x. So it can not be simplified beyond: Root X + root 3x Yes. The square root of 3x equals the square root of 3 times the square root of x, so when you add another square root of x, you can factor out the square root of x, thereby simplifying the expression to the square root of x times the sum of one plus the square root of three.

The square root of the fifth root of x is the tenth root of x.

We use the property of square roots that says the square root of (ab)=square root (a) multiplied by square root of b So square root (4x)=square root (4) mutiplies by square root of x =2(square root (x)) 2sqrt(x)

the square root of x*x is x if there is a 3 then a square root it is acutally cube root. the cube root of x*x*x is x if there is a 4 then a check symbol then that is fourth root. the fourth root of x*x*x*x is x. the square root of 16 is 4(4*4=16). the fourth root of 16 is 2(2*2*2*2=16).

square root of 4x is 2 times square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them

The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).

SQRT(X) * SQRT(X) = X

4

The fraction must be rationalized. Since it is the square root of x in the denominator, you are going to multiply the numerator and denominator by the square root of x. For simplicity of the problem, root will take the place of the symbol for square root: root(3y)/root(x) root(3y)*root(x)/root(x)*root(x) root(3xy)/x The simplified answer is going to be the square root of 3xy divided by x. Hope that helped.

The square root of x squared is x, or x to the first power.

replace square root o x with t.

Square root of (1296) =Square root of (16 x 81)=SQ. root of (16) x Sq. root of (81) =4 x 9 =36

Yes.

x=y

Answer: The difference between the square root of x and squared is either x or -x. Answer: The square root is the inverse function of the square function. That means that it's basically the opposite. Asking for the square root of "x" is like asking "what number must I square to get 'x'".

The derivative of cos x is -sin x, the derivative of square root of x is 1/(2 root(x)). Applying the chain rule, the derivative of cos root(x) is -sin x times 1/(2 root(x)), or - sin x / (2 root x).

It seems to be 25. Call your number "x". x = 5 square root of (5 square root of (5 ...) Square it; this will eliminate the outermost square root sign: x squared = 25 times 5 square root of (5 square root of (... Dividing the second equation by the first one, you get: x squared / x = 25 x / x x = 25

y = sqrt X + 3sqrt X is the same as y = 4 sqrt X

Its the square root of 2 times x Ambiguous. More clear is x times square root of 2

The square root of x can also be written as x^1/2. The cubic root of x is x^1/3, the fourth root x ^1/4, and so on.

(x^2+x-1/2)= x(x+1)-1/2 [x + (1 - square root of 3)/2][x + (1 + square root of 3)/2] = 0 Check it: x^2 + x/2 + (square root of 3)x)/2 + x/2 + 1/4 + (square root of 3)/4 - (square root of 3)x/2 - (square root of 3)/4 - 3/4 = 0 x^2 + x/2 + x/2 + [(square root of 3)x]/2 - [(square root of 3)x]/2 + (square root of 3)/4 - (square root of 3)/4 + 1/4 - 3/4 = 0 x^2 + x - 2/4 = 0 x^2 + x - 1/2 = 0 How to find this roots: Using the completing the square method: x^2 + x - 1/2 = 0 x^2 + x = 1/2 x^2 + x + 1/4 = 1/2 + 1/4 (x + 1/2)^2 = 3/4 x + 1/2 = (plus & minus)(square root of 3/4) x = -1/2 + (square root of 3)/2 x = - 1/2 - (square root of 3)/2

200 times the square root of x

The square root of x = x to the power of a half

: x squared times square root of x : : = x^2 * x^(1/2) : = x^[2+(1/2)] : = x^[(4/2)+(1/2)] : = x^(5/2) : which is the same thing as : square root of (x raised to the 5th power)